Method for measuring content of gold in gold concentrate

Through the methods of fire test enrichment and automatic mineralogical analysis, the complex gold content testing methods in gold concentrate and the health hazards of people are solved, and accurate and safe gold content measurement is achieved, which simplifies the operation process and improves the measurement accuracy.

CN119643804AActive Publication Date: 2025-03-18CHANGCHUN GOLD RES INST

Patent Information

Application Number
CN202510174892.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The gold content testing method in existing gold concentrates is complex in operation, and contact with corrosive acids has great harm to personnel's health, and it is impossible to effectively remove some interfering elements, resulting in errors in the test results.

Method used

The content of gold in gold concentrate was determined by using fire test enrichment and automatic mineralogical analysis. The percentage content and grade of gold were calculated by thermal inlay, curing, grinding and spraying of carbon, combined with the melting treatment of potassium nitrate, sodium carbonate, lead oxide, silica and borax, precious metals were separated and automatic mineralogical analysis was performed to calculate the percentage content and grade of gold.

Benefits of technology

It realizes that no contact with dangerous drugs such as acid and alkali can be achieved, and insoluble impurities can be eliminated and the gold content in gold concentrate can be accurately measured. The operation steps are simple, the measurement time is saved, the data is accurate, and the workload is saved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643804A_ABST
    Figure CN119643804A_ABST
Patent Text Reader

Abstract

The invention provides a method for measuring the content of gold in gold concentrate, and belongs to the technical field of process mineralogy. According to a traditional measuring method, metal is separated by mainly carrying out acid treatment on a sample, so that although silver can be removed, platinum, rhodium and other metals cannot be removed, and the accuracy is influenced. According to the method, the content of gold in the gold concentrate is measured through fire assaying enrichment and automatic mineralogy analysis, and compared with a traditional measuring method, the method does not need to make contact with dangerous drugs such as acid and alkali, insoluble impurities can be removed, and the content of gold in the gold concentrate can be accurately measured. In addition, the test method provided by the invention is simple and convenient in operation steps; drying and measuring are carried out simultaneously, so that measuring time is saved; and by combining automatic mineralogical analysis, the measurement data is accurate, the workload is saved, and reliable data support is provided for efficiently utilizing such resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of process mineralogy, and in particular to a method for measuring the gold content in a gold concentrate. Background Art

[0002] The gold content in gold concentrate is one of the important indicators for evaluating the reserves and value of gold mines. It directly affects the mining and extraction efficiency of gold mines. By measuring the gold content in gold concentrate, we can understand the potential value of gold mines, which is of guiding significance for formulating reasonable mining and extraction plans, optimizing production processes, improving production efficiency, and increasing the economic benefits of gold mines. The gold content in gold concentrate is also an important basis for evaluating the quality of gold ore and the risk of gold price fluctuations, because the level of gold content directly affects the market price and competitiveness of gold ore.

[0003] There are many methods for determining the gold content in gold concentrate, such as fire assay weight method, fire assay enrichment-flame atomic absorption spectrometry, activated carbon enrichment-flame atomic absorption spectrometry, activated carbon enrichment-iodine titration, etc. The above measurement methods generally have more operating steps and the determination of the ingredient amount is more complicated, which requires relevant personnel to be trained before they can operate.

[0004] In the prior art, a method for determining the gold content is provided in the patent with publication number CN104089798A, which includes: (1) burning the sample to be tested in a muffle furnace to remove sulfur, arsenic, carbon and organic matter; (2) adding sodium fluoride and aqua regia to the sample to be tested after burning to dissolve it so as to obtain a solution; (3) adding foam plastic to the solution for adsorption treatment so that the foam plastic absorbs the gold in the solution; (4) taking out the foam plastic after adsorption treatment and burning it to ashing to obtain an ashing product; (5) adding aqua regia, water, phosphoric acid-sodium phosphate solution, potassium bromide solution, diphenylthiourea acetone solution and ethyl acetate to the ashing product in sequence for extraction; (6) separating to obtain an organic phase containing gold; (7) using a flame atomic absorption spectrometer to analyze the organic phase containing gold so as to determine the gold content of the sample to be tested. However, this method requires multiple additions of strong acid for dissolution, which poses certain occupational health hazards to operators. The patent with publication number CN109900678A provides an analytical method for determining the gold content in crude silver. The gold content in crude silver is determined by fire assay gold enrichment-atomic absorption spectrometry, which avoids the interference of other elements in crude silver, has high accuracy, good precision, and a wide measurement range, and is suitable for the determination of the amount of gold in crude silver. This invention has many operating steps and also requires acid for dissolution, which poses certain occupational health hazards to operators. In addition, when nitric acid is used to separate gold, this method cannot eliminate the influence of interfering elements for elements such as platinum and rhodium that are insoluble in nitric acid, which leads to errors in the test results for specific samples containing platinum and rhodium elements. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a method for measuring the gold content in gold concentrate, aiming to solve the problem that the existing method for testing the gold content in gold concentrate is complicated to operate, involves contact with corrosive acids and other substances, poses certain occupational health hazards to personnel, and cannot eliminate some interfering elements, resulting in errors in the test results.

[0006] The present application provides a method for measuring the gold content in a gold concentrate, comprising the following steps: S1. Take m1 g of the sample to be tested, dry it, cool it, and obtain sample a1. Weigh it, record the mass as m2 g, and calculate the weight loss rate w of the sample to be tested, w=m2 / m1; S2. The sample a1 is subjected to hot mounting, curing, grinding and polishing, and carbon spraying to obtain an automatic mineralogical analysis sample, and then an automatic mineralogical analysis is performed to measure the mass fraction of sulfur to be f1 and the mass fraction of copper to be f2; S3. Take the sample m3 g to be tested and grind it to obtain sample a2; S4. The sample a2 is mixed with potassium nitrate, sodium carbonate, lead oxide, silicon dioxide and borax to obtain a sample a3; S5. The sample a3 is added with a silver nitrate solution and covered with a mixture of sodium carbonate and borax on the surface; then melted, cooled, and the precious metal, lead beads and slag are separated; S6. placing the precious metal and lead alloy beads in a preheated magnesia ash dish, heating, cooling, and obtaining alloy particles; S7. The alloy particles are placed in ethanol for a first ultrasonic oscillation, the alloy particles are rolled into thin sheets, and then placed in ethanol for a second ultrasonic oscillation to obtain sample a4, which is dried and weighed, and the mass is recorded as N mg; S8. The sample a4 is subjected to an automatic mineralogical analysis test to obtain the area data of each element, which is recorded as Si1; after the test and analysis, the sample a4 is turned 180°, and the other surface is subjected to an automatic mineralogical analysis test to obtain the area data of each element, which is recorded as Si2; wherein Si1 and Si2 are respectively used to represent the area data of element i on two different surfaces, i=1, 2, 3, ..., n, respectively representing different elements, i=1 represents the gold element, and n is the number of elements measured; Then calculate the gold percentage O in the alloy particles, O=(S11+S12)ρ1 / M; in, , ρi is the density of element i; S9. Calculate the gold grade H in the gold concentrate, H=N*O / ((m3*w)*10 -3 ) g / t.

[0007] In the technical solution of the embodiment of the present application, the present application determines the gold content in the gold concentrate by fire assay enrichment and automatic mineralogical analysis. Compared with the traditional measurement method, the present application does not need to contact dangerous drugs such as acid and alkali, and can remove insoluble impurities and accurately measure the gold content in the gold concentrate. In addition, the test method provided by the present invention has simple operation steps; drying and measurement are carried out simultaneously, saving measurement time; combined with automatic mineralogical analysis, the measurement data is accurate, and the workload is saved, providing reliable data support for the efficient use of such resources.

[0008] In some embodiments, in step S1, the drying temperature is 90-100° C., and the drying time is 1.5-2.0 h.

[0009] In this embodiment, the dry weight of the sample to be tested can be obtained by drying.

[0010] In some embodiments, in step S3, the mass m3 of the sample to be tested is 20-30 g; and the grinding fineness is such that the sample passes through a 320-mesh sieve.

[0011] In this embodiment, the sample to be tested is ground to a certain fineness to facilitate the subsequent processing of the sample.

[0012] In some embodiments, in step S4, the amount of sample a2 added is 23~27g; the theoretical amount of potassium nitrate added is 1.0Q~1.2Q g, wherein Q=600*f1-7, if the theoretical amount added is in the range of 10~30g, the theoretical amount added is used as the actual amount of potassium nitrate added, if the theoretical amount added is <10g, 10g is used as the actual amount of potassium nitrate added, if the theoretical amount added is >30g, 30g is used as the actual amount of potassium nitrate added; the amount of sodium carbonate added is 35~50g; the amount of lead oxide added is 1.0P~1.2P g, wherein P=500*f1+40*f2+30; the amount of silicon dioxide added is 15~30g; the amount of borax added is 10~20g.

[0013] In this embodiment, potassium nitrate, sodium carbonate, lead oxide, silicon dioxide and borax are added to the gold concentrate for melting, which can reduce the melting point of the slag, improve the melt fluidity, promote metal oxidation and separation, reduce sulfide interference, and improve the recovery rate of precious metals such as gold and silver and the accuracy of fire assay through chemical reaction.

[0014] In some embodiments, in step S5, the amount of silver nitrate solution added is 0.5-1.0 ml, and the concentration is 8-12 g / L.

[0015] In this embodiment, by adding silver nitrate solution, it can react with the silver in the sample and dissolve the silver into a soluble silver nitrate solution. Through this dissolution-precipitation method, gold and silver can be effectively separated.

[0016] In some embodiments, in step S5, the mass ratio of sodium carbonate to borax is 2:1.

[0017] In this embodiment, in the fire assay method, sodium carbonate and borax are used as covering agents to prevent melt splashing and dust diffusion, while protecting the equipment from high temperature.

[0018] In some embodiments, in step S5, the melting temperature is 1150-1250° C., and the melting time is 25-30 min.

[0019] In this embodiment, precious metals and lead alloy beads are separated from slag by melting.

[0020] In some embodiments, in step S6, the preheating and heating temperatures are 850-950° C., and the heating time is 2-3 min.

[0021] In this embodiment, the precious metal and lead alloy beads are heated to melt the two to obtain alloy particles.

[0022] In some embodiments, in step S7, the first ultrasonic oscillation lasts for 18 to 22 minutes, and the second ultrasonic oscillation lasts for 8 to 12 minutes.

[0023] In this embodiment, the sample is subjected to ultrasonic treatment to remove surface impurities.

[0024] In some embodiments, in step S7, the thickness of the sheet is 0.01-0.03 mm.

[0025] In this embodiment, the sample is pressed into thin slices to facilitate subsequent mineralogical analysis and testing.

[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 This is a flow chart of the method for measuring the gold content in the gold concentrate in Example 1.

[0029] Figure 2 This is the result of automatic mineralogical analysis of sample a1 in Example 1.

[0030] Figure 3 This is a physical picture of the automatic mineralogical analysis sample of sample a4 in Example 1.

[0031] Figure 4 This is the automatic mineralogical analysis test diagram of sample a4 in Example 1. DETAILED DESCRIPTION

[0032] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0033] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0034] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0035] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0036] In order to solve the problem that the existing gold content test method in gold concentrate is complicated to operate, contacts corrosive acids and other substances, has certain occupational health hazards to personnel, and cannot remove some interfering elements, resulting in errors in the test results, the present application provides a method for testing the gold content in gold concentrate. The traditional measurement method mainly separates metals by acid treatment of the sample. Although silver can be removed, platinum, rhodium and other metals cannot be removed, affecting the accuracy. The present application determines the gold content in the gold concentrate by fire assay enrichment and automatic mineralogical analysis. Compared with the traditional measurement method, the present application does not need to contact dangerous drugs such as acids and alkalis, and can remove insoluble impurities and accurately measure the gold content in the gold concentrate. In addition, the test method provided by the present invention has simple operation steps; drying and measurement are carried out simultaneously, saving measurement time; combined with automatic mineralogical analysis, the measurement data is accurate, while saving workload, providing reliable data support for the efficient use of such resources.

[0037] The present application provides a method for measuring the gold content in a gold concentrate, comprising the following steps: S1. Take m1 g of the sample to be tested, dry it, cool it, and obtain sample a1. Weigh it, record the mass as m2 g, and calculate the weight loss rate w of the sample to be tested, w=m2 / m1; S2. The sample a1 is subjected to hot mounting, curing, grinding and polishing, and carbon spraying to obtain an automatic mineralogical analysis sample, and then an automatic mineralogical analysis is performed to measure the mass fraction of sulfur to be f1 and the mass fraction of copper to be f2; S3. Take the sample m3 g to be tested and grind it to obtain sample a2; S4. The sample a2 is mixed with potassium nitrate, sodium carbonate, lead oxide, silicon dioxide and borax to obtain a sample a3; S5. The sample a3 is added with a silver nitrate solution and covered with a mixture of sodium carbonate and borax on the surface; then melted, cooled, and the precious metal, lead beads and slag are separated; S6. placing the precious metal and lead alloy beads in a preheated magnesia ash dish, heating, cooling, and obtaining alloy particles; S7. The alloy particles are placed in ethanol for a first ultrasonic oscillation, the alloy particles are rolled into thin sheets, and then placed in ethanol for a second ultrasonic oscillation to obtain sample a4, which is dried and weighed, and the mass is recorded as N mg; S8. The sample a4 is subjected to an automatic mineralogical analysis test to obtain the area data of each element, which is recorded as Si1; after the test and analysis, the sample a4 is turned 180°, and the other surface is subjected to an automatic mineralogical analysis test to obtain the area data of each element, which is recorded as Si2; wherein Si1 and Si2 are respectively used to represent the area data of element i on two different surfaces, i=1, 2, 3, ..., n, respectively representing different elements, i=1 represents the gold element, and n is the number of elements measured; Then calculate the gold percentage O in the alloy particles, O=(S11+S12)ρ1 / M; in, , ρi is the density of element i; S9. Calculate the gold grade H in the gold concentrate, H=N*O / ((m3*w)*10 -3 ) g / t.

[0038] In the technical solution of the embodiment of the present application, the gold content in the gold concentrate is determined by fire assay enrichment and automatic mineralogical analysis. Compared with the traditional measurement method, it does not require contact with dangerous drugs such as acids and alkalis, and can remove insoluble impurities to accurately measure the gold content in the gold concentrate. In addition, the test method has simple operation steps; drying and measurement are carried out simultaneously, saving measurement time; combined with automatic mineralogical analysis, the measurement data is accurate, and the workload is saved, providing reliable data support for the efficient use of such resources.

[0039] Furthermore, in some embodiments, in step S1, the drying temperature is 90-100° C., and the drying time is 1.5-2.0 h.

[0040] In the technical solution of the embodiment of the present application, the dry weight of the sample to be tested can be obtained by drying.

[0041] Furthermore, in some embodiments, in step S2, the hot mounting refers to mixing the sample and the mounting material in a specific mass ratio and then heating and pressing the sample; the mounting material is a thermosetting phenolic epoxy resin with a particle size of 5 to 10 μm, and the mass ratio of the sample to the mounting material is 1:2 to 1:5.

[0042] Furthermore, in some embodiments, in step S3, the mass m3 of the sample to be tested is 20-30 g; and the grinding fineness is such that the sample can pass through a 320-mesh sieve.

[0043] In the technical solution of the embodiment of the present application, by grinding the sample to be tested to a certain fineness, it is convenient for the subsequent processing of the sample.

[0044] Further, in some embodiments, in step S4, the amount of sample a2 added is 23~27g; the theoretical amount of potassium nitrate added is 1.0Q~1.2Q g, wherein Q=600*f1-7, if the theoretical amount added is in the range of 10~30g, the theoretical amount added is used as the actual amount of potassium nitrate added, if the theoretical amount added is <10g, 10g is used as the actual amount of potassium nitrate added, if the theoretical amount added is >30g, 30g is used as the actual amount of potassium nitrate added; the amount of sodium carbonate added is 35~50g; the amount of lead oxide added is 1.0P~1.2P g, wherein P=500*f1+40*f2+30; the amount of silicon dioxide added is 15~30g; the amount of borax added is 10~20g.

[0045] In the technical solution of the embodiment of the present application, potassium nitrate, sodium carbonate, lead oxide, silicon dioxide and borax are added to the gold concentrate for melting, which can reduce the melting point of the slag, improve the fluidity of the melt, promote metal oxidation and separation, reduce sulfide interference, and improve the recovery rate of precious metals such as gold and silver and the accuracy of the fire assay method through chemical reactions.

[0046] Furthermore, in some embodiments, in step S5, the amount of silver nitrate solution added is 0.5-1.0 ml, and the concentration is 8-12 g / L.

[0047] In the technical solution of the embodiment of the present application, by adding silver nitrate solution, it is possible to react with the silver in the sample and dissolve the silver into a soluble silver nitrate solution. Through this dissolution-precipitation method, gold and silver can be effectively separated.

[0048] Furthermore, in some embodiments, in step S5, the mass ratio of sodium carbonate to borax is 2:1.

[0049] In the technical solution of the embodiment of the present application, in the fire assay method, sodium carbonate and borax are used as covering agents to prevent melt splashing and dust diffusion, while protecting the equipment from high temperature.

[0050] Furthermore, in some embodiments, in step S5, the melting temperature is 1150-1250° C., and the melting time is 25-30 min.

[0051] In the technical solution of the embodiment of the present application, precious metals, lead alloy beads and slag are separated by melting.

[0052] Furthermore, in some embodiments, in step S6, the preheating and heating temperatures are 850-950° C., and the heating time is 2-3 min.

[0053] In the technical solution of the embodiment of the present application, the precious metal and lead alloy beads are heated to melt the two to obtain alloy particles.

[0054] Furthermore, in some embodiments, in step S6, the magnesia ash dish is obtained by mixing and evenly pressing No. 425 cement, magnesia with a particle size of ≤0.18 mm and water in a mass ratio of 15:85:10.

[0055] Furthermore, in some embodiments, in step S7, the time of the first ultrasonic oscillation is 18 to 22 minutes, and the time of the second ultrasonic oscillation is 8 to 12 minutes.

[0056] In the technical solution of the embodiment of the present application, the sample is subjected to ultrasonic treatment to remove surface impurities.

[0057] Furthermore, in some embodiments, in step S7, the thickness of the sheet is 0.01-0.03 mm.

[0058] In the technical solution of the embodiment of the present application, the sample is pressed into thin slices to facilitate subsequent mineralogical analysis and testing.

[0059] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0060] Example 1 This embodiment provides a method for testing the gold content in gold concentrate. Figure 1 As shown, the specific steps include: (1) Weigh 1000 g of the sample to be tested and dry it in a 90 °C oven for 1.5 h. After drying, cool it to room temperature to obtain sample a1, which has a mass of 991 g. The weight loss rate of the sample is w, so w = m3 / m2 = 991 / 1000 = 0.991.

[0061] (2) Weigh 4 g of the dried sample and mix it with 8 g of thermosetting phenolic epoxy resin with a particle size of 5 μm. Press the sample at 125°C and 220 Bar. After curing, grind and polish, carbon spray, and then perform automatic mineralogical analysis. The test results are shown in the figure below. Figure 2 As shown, the mass fraction of sulfur and the mass fraction of copper were measured to be 26.00% and 1.40%.

[0062] (3) Weigh 25 g of the sample to be tested and grind it to a fineness that allows it to pass through a 320-mesh sieve, thereby obtaining sample a2.

[0063] (4) Add 30 g of potassium nitrate, 35 g of sodium carbonate, 170 g of lead oxide, 15 g of silicon dioxide, and 10 g of borax to sample a2 and mix to obtain sample a3.

[0064] (5) Place sample a3 in a clay crucible, add 0.5 ml of 10 g / L silver nitrate solution, and cover the surface with 8 g of a mixture of sodium carbonate and borax in a mass ratio of 2:1. Place it in an electric furnace and set the temperature to 1200°C. After the temperature reaches the preset temperature, continue melting for 25 minutes. Take out the clay crucible, rotate and vibrate it 5 times to make the lead and precious metal beads sink, pour out the molten material, cool it, and tap it to separate the precious metal and lead beads from the slag.

[0065] (6) Preheat the magnesia ash dish at 900°C for 20 min, then place the precious metal and lead alloy beads in it, continue heating for 3 min, and then cool to obtain alloy particles.

[0066] (7) The alloy particles were taken out and ultrasonically vibrated in ethanol for 20 min. The alloy particles were then rolled into a thin sheet with a thickness of 0.02 mm and ultrasonically vibrated in ethanol again for 10 min to obtain sample a4. The sample was dried and weighed, and its mass was 0.87 mg.

[0067] (8) Figure 3 As shown, the sample a4 is placed on the conductive glue and tested and analyzed in an automatic mineralogy analysis instrument. The test diagram is shown in FIG. Figure 4 As shown, the area data of each element is measured, which is recorded as Si1; after the test and analysis, the sample a4 is turned 180°, and the other surface is subjected to automatic mineralogical analysis test to obtain the area data of each element, which is recorded as Si2; wherein Si1 and Si2 are respectively used to represent the area data of element i on two different surfaces, i=1, 2, respectively representing the gold element and the silver element; Then calculate the gold percentage O in the alloy particles, O=(S11+S12)ρ1 / M; in, , ρi is the density of element i; for example Figure 4 The sample description and analysis and calculation results are shown in Table 1.

[0068] Table 1 Calculation results of automatic mineralogical analysis of sample 1 (9) Calculate the gold grade H in gold concentrate, H = N*O / ((m3*w)*10 -3 )g / t=0.87*95.56% / 25 / 0.991 / 10 -3 g / t=33.56g / t.

[0069] Example 2 This embodiment provides a method for testing the gold content in gold concentrate. Figure 1 As shown, the specific steps include: (1) Weigh 500 g of the sample to be tested and dry it in a 95 °C oven for 1.5 h. After drying, cool it to room temperature to obtain sample a1, which has a mass of 496 g. The weight loss rate of the sample is w, so w = m3 / m2 = 496 / 500 = 0.992.

[0070] (2) Weigh 3.5 g of the dried sample and mix it with 7 g of a thermosetting phenolic epoxy resin with a particle size of 5 μm. Press the sample at 130°C and 230 Bar. After curing, grind and polish, and carbon spray. Then, perform automatic mineralogical analysis. The mass fraction of sulfur and copper were measured to be 23.55% and 2.10%, respectively.

[0071] (3) Weigh 25 g of the sample to be tested and grind it to a fineness that allows it to pass through a 320-mesh sieve to obtain sample a2.

[0072] (4) Add 30 g of potassium nitrate, 35 g of sodium carbonate, 170 g of lead oxide, 15 g of silicon dioxide, and 10 g of borax to sample a2 and mix to obtain sample a3.

[0073] (5) Place sample a3 in a clay crucible, add 0.5 ml of 10 g / L silver nitrate solution, and cover the surface with 10 g of a mixture of sodium carbonate and borax in a mass ratio of 2:1. Place it in an electric furnace and set the temperature to 1200°C. After the temperature reaches the preset temperature, continue melting for 25 minutes. Take out the clay crucible, rotate and vibrate it 5 times to make the lead and precious metal beads sink, pour out the melt, cool it, and tap it to separate the precious metal and lead beads from the slag.

[0074] (6) Preheat the magnesia ash dish at 900°C for 20 min, then place the precious metal and lead alloy beads in it, continue heating for 3 min, and then cool to obtain alloy particles.

[0075] (7) The alloy particles were taken out and ultrasonically vibrated in ethanol for 20 min. The alloy particles were then rolled into a thin sheet with a thickness of 0.02 mm and ultrasonically vibrated in ethanol again for 10 min to obtain sample a4. The sample was dried and weighed, and its mass was 0.45 mg.

[0076] (8) placing the sample a4 on a conductive adhesive, and performing a test and analysis in an automatic mineralogical analysis instrument to obtain the area data of each element, which is recorded as Si1; after the test and analysis, turning the sample a4 180°, and performing an automatic mineralogical analysis test on the other surface to obtain the area data of each element, which is recorded as Si2; wherein Si1 and Si2 are respectively used to represent the area data of element i on two different surfaces, and i=1, 2, 3 are respectively used to represent gold, silver, and platinum; Then calculate the gold percentage O in the alloy particles, O=(S11+S12)ρ1 / M; in, , ρi is the density of element i; the analysis and calculation results are shown in Table 2.

[0077] Table 2 Calculation results of automatic mineralogical analysis of sample 2 (10) Calculate the gold grade H in gold concentrate, H = N*O / ((m3*w)*10 -3 )g / t=0.45*93.03% / 25 / 0.992 / 10 -3 g / t=16.88 g / t.

[0078] According to GB / T20899.1-20149 “Chemical Analysis Methods for Gold Ore”, the gold content in the samples in Example 1 and Example 2 was tested, and the test results were 33.60 g / t and 17.65 g / t, respectively.

[0079] By comparing the test results of the gold content of the samples in Example 1 and Example 2 obtained according to the present application scheme and the national standard test method, it can be seen that the test results of the gold content according to the national standard test method are all on the high side. This is because when treated with acid, the acid-insoluble elements such as platinum and rhodium in the samples are not separated, and a small amount of impurities such as unprocessed silver exist, which makes the test results high.

[0080] In summary, the present application provides a method for testing the gold content in gold concentrate. Traditional measurement methods mainly separate metals by subjecting samples to acid treatment. Although this can remove silver, it cannot remove metals such as platinum and rhodium, which affects the accuracy. The present application determines the gold content in gold concentrate by fire assay enrichment and automatic mineralogical analysis. Compared with traditional measurement methods, the present application does not require contact with dangerous drugs such as acids and alkalis, and can remove insoluble impurities to accurately measure the gold content in gold concentrate. In addition, the test method provided by the present invention has simple operating steps; drying and measurement are carried out simultaneously, saving measurement time; combined with automatic mineralogical analysis, the measurement data is accurate and workload is saved, providing reliable data support for the efficient use of such resources.

[0081] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for measuring the gold content in a gold concentrate, characterized in that: The following steps are involved: S1. Take m1 g of the sample to be tested, dry it, cool it, and obtain sample a1. Weigh it, record the mass as m2 g, and calculate the weight loss rate w of the sample to be tested, w=m2 / m1; S2. The sample a1 is subjected to hot mounting, curing, grinding and polishing, and carbon spraying to obtain an automatic mineralogical analysis sample, and then an automatic mineralogical analysis is performed to measure the mass fraction of sulfur to be f1 and the mass fraction of copper to be f2; S3. Take the sample m3 g to be tested and grind it to obtain sample a2; S4. The sample a2 is mixed with potassium nitrate, sodium carbonate, lead oxide, silicon dioxide and borax to obtain a sample a3; S5. The sample a3 is added with a silver nitrate solution and covered with a mixture of sodium carbonate and borax on the surface; then melted, cooled, and the precious metal, lead beads and slag are separated; S6. placing the precious metal and lead alloy beads in a preheated magnesia ash dish, heating, cooling, and obtaining alloy particles; S7. The alloy particles are placed in ethanol for a first ultrasonic oscillation, the alloy particles are rolled into thin sheets, and then placed in ethanol for a second ultrasonic oscillation to obtain sample a4, which is dried and weighed, and the mass is recorded as N mg; S8. The sample a4 is subjected to automatic mineralogical analysis and testing to obtain the area data of each element, recorded as Si1; After the test and analysis, the sample a4 is turned 180°, and the other surface is subjected to automatic mineralogical analysis test to obtain the area data of each element, which is recorded as Si2; wherein Si1 and Si2 are respectively used to represent the area data of element i on two different surfaces, i=1, 2, 3, ..., n, respectively used to represent different elements, i=1 represents the gold element, and n is the number of elements measured; Then calculate the gold percentage O in the alloy particles, O=(S11+S12)ρ1 / M; in, , ρi is the density of element i; S9. Calculate the gold grade H in the gold concentrate, H=N*O / ((m3*w)*10 -3 ) g / t.

2. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S1, the drying temperature is 90-100° C., and the drying time is 1.5-2.0 h.

3. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S3, the mass m3 of the sample to be tested is 20-30 g; the grinding fineness is that the sample can pass through a 320-mesh sieve.

4. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S4, the added amount of the sample a2 is 23~27g; the theoretical added amount of potassium nitrate is 1.0Q~1.2Q g, wherein Q=600*f1-7, if the theoretical added amount is in the range of 10~30g, the theoretical added amount is used as the actual added amount of potassium nitrate, if the theoretical added amount is less than 10g, 10g is used as the actual added amount of potassium nitrate, if the theoretical added amount is greater than 30g, 30g is used as the actual added amount of potassium nitrate; the added amount of sodium carbonate is 35~50g; the added amount of lead oxide is 1.0P~1.2P g, wherein P=500*f1+40*f2+30; the added amount of silicon dioxide is 15~30g; the added amount of borax is 10~20g.

5. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S5, the amount of silver nitrate solution added is 0.5-1.0 ml, and the concentration is 8-12 g / L.

6. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S5, the mass ratio of sodium carbonate to borax is 2:

1.

7. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S5, the melting temperature is 1150-1250° C., and the melting time is 25-30 min.

8. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S6, the preheating and heating temperatures are 850-950° C., and the heating time is 2-3 min.

9. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S7, the first ultrasonic oscillation time is 18-22 minutes, and the second ultrasonic oscillation time is 8-12 minutes.

10. The method for measuring the gold content in gold concentrate according to claim 1, characterized in that: In step S7, the thickness of the sheet is 0.01-0.03 mm.

Citation Information

Patent Citations

  • Gold content determination method

    CN104089798A

  • Analysis method for measuring content of gold in crude silver

    CN109900678A

  • Binary system gold ore gold-bearing mineral gold content determination method

    CN115656464A

  • Method for measuring granularity of metallic mineral

    CN118937169A

  • Method for measuring three-dimensional form of gold mineral

    CN119164737A

Cited By

  • Method for measuring content of carbonate minerals

    CN119880953A